Barriers to mental health service utilization among African immigrants in the United Kingdom: A systematic review - Archibong Bassey; Rachael Zaka (Wiley, 2024)
Abstract Background African immigrants in the United Kingdom (UK) face unique challenges in accessing mental health services (MHSs), in contrast to their peers born in the UK, contributing to their worsening mental and physical health outcomes. This study aims to uncover barriers to MHS utilization and proffer evidence‐based recommendations toward addressing the mental health needs of African immigrants residing in the UK. Methods A systematic literature search was conducted across six databases: Medline, PsycINFO, Web of Science, CIHNAL, Scopus, and Embase published up to September 2022. To assess methodological quality of the included studies, the Critical Appraisal Skills Program qualitative checklist and the Mixed Methods Appraisal Tool Version 2018 were used. Consecutively, a deductive thematic analysis was employed to group related barriers within overarching themes. Results The study selection process yielded eight studies conducted in the UK, encompassing African populations identifying as African/Afro‐Caribbean origin, Somali refugees, and ethnic minorities of Black/British descent. The findings highlight the complex interplay of key barriers such as stigma, residential instability, cultural influences, discrimination, and accessibility issues, among others, that continue to hinder African populations from accessing and utilizing MHSs. These barriers were categorized into predisposing,enabling and need factors (themes), aligning with Anderson's model of health service utilization, reflecting a comprehensive range of challenges affecting this population. Conclusion This systematic review illuminates the myriad barriers faced by African immigrants in utilizing MHSs in the UK, underlining the urgent need for targeted interventions. The findings advocate for the development of culturally sensitive, affordable, and accessible MHSs and policies that address the personal, sociocultural, and structural barriers identified. Collaboration across key stakeholders is highly recommended for advancing equitable and inclusive MHSs for all.